2022
DOI: 10.3390/en15155448
|View full text |Cite
|
Sign up to set email alerts
|

Financial Situation of Local Government Units as a Determinant of the Standards of Living for the Polish Population

Abstract: In this paper, the author intends to show the interaction between the living standards of the population and the financial situation of Polish local government units at the commune level. The first (theoretical) part of the paper provides a synthetic description of topics related to defining the economic terms and to the local government’s ability to impact the standards of living of the local population. In view of the multifaceted nature of terms covered by this analysis, the second part uses a canonical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Transport-related social exclusion, the "legacy burden" of communistera farmland control policies ("PGR" state agricultural farms) [61], combined with reduced labor demand and a progressively ageing population , all act as barriers to local growth. This trend is corroborated by past studies [9,[62][63][64][65].…”
Section: Small Towns and Their Functions In The Warmi ńSko-mazurskie ...supporting
confidence: 89%
“…Transport-related social exclusion, the "legacy burden" of communistera farmland control policies ("PGR" state agricultural farms) [61], combined with reduced labor demand and a progressively ageing population , all act as barriers to local growth. This trend is corroborated by past studies [9,[62][63][64][65].…”
Section: Small Towns and Their Functions In The Warmi ńSko-mazurskie ...supporting
confidence: 89%
“…The calculated redundancy index (over 29%) is moderately high. This can be compared with another research project [91] carried out for all commune types in Poland. It used 35 sub-metrics (relating, e.g., to incomes, expenditure, or debt), and found that if the values of variables representing the financial condition are known, they can explain 32.34% of the variance in the set related to the living standards of the residents.…”
Section: Discussionmentioning
confidence: 99%
“…Phillips and Strickland (2016) showed that the degree of debt, as a category of fiscal distress, is correlated with a lower likelihood of implementing environmental programs. In turn, Malinowski (2022) found inverse relationships between the debt burden and the cleanliness of the natural environment.…”
Section: Debt Burdenmentioning
confidence: 92%
“…Brzozowska et al (2022), analysing the municipalities in Poland, noticed that high expenditures for environmental protection and municipal services management are in units which are adjacent to protected wildlife areas and those suffering from pollution. Moreover, Malinowski (2022) disclosed ties between the cleanliness of the natural environment and the growth in the self-financing ratio of the local government (positive relation), and the debt burden (negative relation). As a result, increases in environmental expenditures by municipalities are closely related to an improvement in financial health (Dziekański, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%